Exploring Head Teachers’ Instructional Supervisory Role: The Case of Public Junior High Schools in Jirapa Municipality of Ghana - Ghanney, Robert Andrews; Nuobalee, Jeremiah (American Journal of Education and Learning, 2021)
The study explored Head teachers’ instructional supervisory role among public Junior High Schools in the Jirapa Municipality of the Upper West Region of Ghana. It adopted psychological and system theory of supervision propounded by Planturrroot (2006) and Bertalanffy (2015) respectively. The mixed method sequential approach was followed in the conduct of the study where both quantitative and qualitative data were collected and analysed. A sample size of 200 respondents made up of 40 head teachers, 80 teachers and 80 pupils were used for the quantitative data, whilst 10 head teachers were selected for the qualitative data. The Statistical Product for Service Solutions (SPSS) version 23 was used to analyse the quantitative data while thematic approach was used for the qualitative data. The findings of the study revealed in-frequent orientation for newly engaged teachers. It further showed lower ratings in the provision of in-service training, time tabling design and setting of performance target for pupils and teachers. It was recommended that the Ministry of Education and Ghana Education Service (GES) should regularly organize workshops, seminars and in-service trainings on supervisory roles of head teachers and assistant head teachers to equip them with the needed knowledge and skills in the municipality. Lastly, Heads of schools and other supervisors should re-design schools` time tables to suit the use of instructional time in the lesson of teachers to enhance their monitoring.